Age and postoperative opioid prescriptions: a population‐based cohort study of opioid‐naïve adults. Issue 4 (13th February 2020) - Bethell, Jennifer; Neuman, Mark D.; Bateman, Brian T.; Hill, Andrea D.; Ladha, Karim S.; Wijeysundera, Duminda N.; Wunsch, Hannah
Abstract: Purpose: Opioids are commonly prescribed for acute pain after surgery. However, it is unclear whether these prescriptions are usually modified to account for patient age and, in particular, opioid‐related risks among older adults. We therefore sought to describe postoperative opioid prescriptions filled by opioid‐naïve adults undergoing four common surgical procedures. Methods: This retrospective cohort study used individually linked surgery and prescription opioid dispensing data from Ontario, Canada to create a population‐based sample of 135 659 opioid‐naïve adults who underwent one of four surgical procedures (laparoscopic cholecystectomy, laparoscopic appendectomy, knee meniscectomy, or breast excision) between 2013 and 2017. Patient age, in years, was categorized as 18 to 64, 65 to 69, 70 to 74, and 75 and over. Postoperative opioid prescriptions were identified as those filled on or within 6 days of surgical discharge date. For those who filled a prescription, we assessed the total morphine milligram equivalent (MME) dose, types of opioids, and any subsequent opioid prescriptions filled within 30 days of surgical discharge date. Results were presented stratified by surgical procedure. Results: For three of the four surgical procedures we assessed, the proportion of patients who filled a postoperative opioid prescription decreased with age ( P < 0.001 for trend), and there was a small shift in the type of opioid (more codeine or tramadol and less oxycodone; P < 0.001 for trend). However, the total MME dose of the initial prescription(s) filled showed minimal age‐related trends. Conclusions: The proportion of opioid‐naïve patients filling postoperative opioid prescriptions decreases with age. However, postoperative opioid prescription dosage is not typically different in older adults.